Comparison Of Different Media Formulations On Growth, Morphology And Chlorophyll Content Of Green Alga, Chlorella Vulgaris - REKHA SHARMA,; GAJENDRA PAL SINGH,; VIJENDRA K. SHARMA, (International Journal of Pharma and Bio Sciences, 2011)
Chlorella vulgaris is a green, spherical, single celled fresh water microalga belongs to the phylum Chlorophyta. As per the study conducted so far it is found that green algae are the highest source of chlorophyll in the plant world and particularly, Chlorella one of the members of green algae is the richest source of chlorophyll which is widely used as a health food and feed supplement, as well as in the pharmaceutical and cosmetics industry. Chlorella has been produced commercially in several countries for its use as neutraceutical food and medicinal purpose due to its valuable contents particularly pigments and proteins. The aim of this work is to evaluate the effect of five different defined inorganic medium such as Juller’s medium, Bold’s basal medium, modified Chu-10 medium, N-8 medium, and Kuhl’s medium, on the growth, morphology and pigment content of C. vulgaris. The best growth was obtained in modified Chu-10 medium as compared to other medium.